Tsunami & Forced Korteweg de Vries Equation - Ong, Chee Tiong; Loi, Wei Sen; Choy, Yaan Yee; Tay, Kim Gaik (2011)
A systematic and comprehensive study of forced solitons in Tsunami waves that can be modelled mathematically by forced Korteweg-de Vries (fKdV). This equation have lost the translation-invariant type of group symmetries due to forcing. The traditional group-theoretical such as inverse scattering method, Backlund transformations and other known approaches can no longer generate analytic solutions of solitons, because there are no infinitely many conservation laws. Numerical simulations and approximate solutions seem the only ways to solve the forced nonlinear evolution equations. Numerical simulations of forced solitons will be implemented by a user-friendly software package FORSO. In this paper we show how approximate scheme can be used to generate forced solitons. Approximate solution also gives various profiles of fKdV such as the depth of depression zone; , amplitude; , speed; s and the period; of generation of forced solitons in Tsunami waves.